2022
DOI: 10.3389/fnagi.2022.950188
|View full text |Cite
|
Sign up to set email alerts
|

Early alteration of peripheral blood lymphocyte subsets as a risk factor for delirium in critically ill patients after cardiac surgery: A prospective observational study

Abstract: ObjectiveThere is a high incidence of delirium among patients with organ dysfunction undergoing cardiac surgery who need critical care. This study aimed to explore the risk factors for delirium in critically ill patients undergoing cardiac surgery and the predictive value of related risk factors.MethodsWe conducted a prospective observational study on adult critically ill patients who underwent cardiac surgery between January 2019 and August 2021. Patients were consecutively assigned to delirium and non-deliri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…(27)(28)(29), which is consistent with our results. Interestingly, the current study showed that patients with POD had lower lymphocytes, which can contribute to the proinflammatory response, which is a mechanism of POD (30). PD involves both motor and non-motor symptoms due to dopaminergic neuron death and α-synuclein aggregation (31).…”
Section: Discussionmentioning
confidence: 56%
“…(27)(28)(29), which is consistent with our results. Interestingly, the current study showed that patients with POD had lower lymphocytes, which can contribute to the proinflammatory response, which is a mechanism of POD (30). PD involves both motor and non-motor symptoms due to dopaminergic neuron death and α-synuclein aggregation (31).…”
Section: Discussionmentioning
confidence: 56%
“…As a result, this could lead to a significant drop in CD8+ T-cells and lymphocytes in COVID-19 critical patients ( 37 ). Furthermore, critical patients had significantly lower T-cell, B-cell, and NK cell counts compared to controls ( 38 ). A gradual decrease in peripheral blood lymphocytes is a common early indicator of adult patients with non-critical and critical illnesses ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between inflammation, immune cells, and the onset of delirium in patients undergoing cardiac surgery remains poorly understood. Li et al [ 8 ] found that levels of peripheral blood lymphocyte subsets were independently associated with delirium and could predict its occurrence in critically ill patients undergoing cardiac surgery. Furthermore, a pilot study indicated that an increased neutrophil-lymphocyte ratio (NLR) may serve as a marker for delirium during the perioperative period [ 9 ].…”
Section: Introductionmentioning
confidence: 99%